2011
DOI: 10.2340/16501977-0642
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of functioning in the acute hospital: operationalisation and reliability testing of ICF categories relevant for physical therapists interventions

Abstract: The study supports that the ICF is adaptable to professional and setting-specific needs of physiotherapists. Further research towards the development of reliable instruments for physiotherapists based on the ICF seems justified. :

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
1
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 0 publications
0
8
1
1
Order By: Relevance
“…The low concordance for the emotional health block observed in this research could be explained by the difficulty of encoding the contents related to the Chapter of Mental Functions (b1) of the ICF, resulting from the degree of subjectiveness of these concepts. Furthermore, the reproducibility between raters in the content encoding process shows variations 66,67 or values below or above the ones found both here and in various other studies [68][69][70] , mentioned even in differentiated variations, according to the chapter of each of the ICF's domains 71 . The noncoverage of the content was reported in another research, which has analyzed eight scales and found non-coverage percentages raging from 0 to 30% 11 , among them all.…”
Section: Discussioncontrasting
confidence: 56%
“…The low concordance for the emotional health block observed in this research could be explained by the difficulty of encoding the contents related to the Chapter of Mental Functions (b1) of the ICF, resulting from the degree of subjectiveness of these concepts. Furthermore, the reproducibility between raters in the content encoding process shows variations 66,67 or values below or above the ones found both here and in various other studies [68][69][70] , mentioned even in differentiated variations, according to the chapter of each of the ICF's domains 71 . The noncoverage of the content was reported in another research, which has analyzed eight scales and found non-coverage percentages raging from 0 to 30% 11 , among them all.…”
Section: Discussioncontrasting
confidence: 56%
“…For example, poor inter-rater reliability for ICF category ratings, such as those for the LBP Core Set (39), has been a source of criticism for the operationalization of Core Sets in clinical practice (40). However, recent work has suggested that reliability may approach levels required for clinical practice when the qualifier levels are reduced and additional definition is provided for each graduation (41). This study has some limitations that warrant consideration and reveal directions for future research.…”
Section: Discussionmentioning
confidence: 92%
“…Secondly, definitions can be given to each response option to further clarify its uniqueness using written descriptions (16) or pictorial presentation (12). Thirdly, the test process can be further standardized in terms of the sequence for collecting or reviewing specific types of information, and the associated decision -making and consensus processes (36). Last, but not least, self-rating by the patient may form one type of information to be considered.…”
Section: Discussionmentioning
confidence: 99%